The knot of happiness in the socio-cultural space of Tuva - Lamazhaa, Chimiza K.; Mainy, Shenne B. (The New Research of Tuva, 2025)
The article compiles and systematizes examples of the dissemination of the ornament “ölçey udazyny” (‘knot of happiness’) in the sociocultural life of Tuva (Russia).The analysis is based on field materials (including photographs) collected by the authors during 2023–2024 in the city of Kyzyl and other areas of the Republic of Tuva, as well as information distributed through mass media and social networks. Drawing on a review of scholarly literature, the article discusses the etymology of the term, the question of its emergence in Tuva, and the extent of its academic study. It is noted that the Tuvan ornament, which is widely spread across Asia and beyond, once again attests to Tuva’s inclusion in the cultural spheres of Buddhism and broader Asian traditions.Today, administrative buildings, public and entertainment facilities, commercial, industrial and residential structures, fences, railings, and other objects in the city of Kyzyl are abundantly decorated with various ornamental motifs —primarily with “ölçey udazyny”. The study demonstrates that this ornament appears in decorative and applied arts, clothing, jewelry, souvenirs, logos, and emblems.It is concluded that the ornament has become one of the vivid expressions of Tuvan ethnocultural self-identification and self-representation and is also understood as a shared marker of Tuva’s cultural world for all its inhabitants. The widespread use of the ornament, including in the ethno-industrial sector, suggests that by expanding the traditional spaces of its existence, it is currently experiencing a period of flourishing and heightened demand.
Keywords: Tuva; Kyzyl; Tuvan culture; ornament; pattern; ölçey udazyny; endless knot; knot of happiness